Braudel revisited : the Mediterranean world, 1600-1800 - Ruiz, Teofilo F., 1943-; Symcox, Geoffrey; Piterberg, Gabriel, 1955- (UCLA Clark Memorial Library series, 2010)
"Fernand Braudel (1912-1985), was a leading French historian and author of, among other books, the groundbreaking The Mediterranean and the Mediterranean World in the Age of Philip II (1949). One of the founders of the Annales School in France, Braudel insisted on treating the Mediterranean region as a whole, irrespective of religious and national divides. Braudel's new historiography rejected political history as the dominant discipline and espoused a 'total history' or a 'history from below' that would tell the story of the vast majority of humanity hitherto excluded from the grand narrative. At the time of the book's appearance, this premise was revolutionary